Association of Liver X Receptor Alpha (LXRα) gene related to characteristic of carcass, meat quality and fatty acid composition in ducks - Gunawan, A.; Azmi, N.; Anggraeni, A. (Diponegoro University, 2021)
Liver X Receptor Alpha (LXRα) is a nuclear receptor that play a crucial role in regulating of gene involvedin lipid metabolism. The aim of this research was to identify polymorphisms and association of LXRα gene with charateristic of carcass, meat quality and fatty acid composition in ducks using Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP). A total sample of 98 Cihateup ducks consisted of 57 females and 41 males with age 12 weeks were used in this study. Product size is 661 bp amplicons. The genotype genes frequencies in CC, GC and GG were 0.21, 0.55 and 0.23 respectively. The chi-square test revealed that LXRα gene (g.3575 C>G) in exon 2 was in Hardy-Weinberg equilibrium. A SNP of LXRα gene in region g.3575 C>G was significantly associated (P<0.05) with duck meat quality and fatty acid content. Several parameters have significant affect (P <0. 05) on meat quality in the breast meat weight, carcass percentage and head percentage, while associated fatty acids were saturated fatty acids (SFA) such as palimitic acid (C16:0); γ-and unsaturated fatty acids (UFA) such as linolenic acid (C18:3n3); cis 11 eicosenoic acid (C20:1) and 11.14 cis-eicosedenoic acid (C20:2). In could be concluded that LXRα gene might be useful as genetic markers to select and produce meat with desirable unsaturated fatty acids.